Mimesis, movies, and media - Cowdell, Scott (Violence, desire, and the sacred, 2015)
Introduction -- Media and representation. On the one medium / Eric Gans -- The scapegoat mechanism and the media: beyond the folk devil paradigm / John O'Carroll -- The apocalypse will not be televised / Chris Fleming -- Film. Mirrors of nature: artificial agents in real life and virtual worlds / Paul Dumouchel -- Superheroes, scapegoats, and saviors: the problem of evil and the need for redemption / Joel Hodge -- Sanctified victimage on page and screen: The hunger games as prophetic media / Debra E. Macdonald -- The mimetic e-motion: from The matrix to Avatar / Nidesh Lawtoo -- Apocalypse of the therapeutic: The cabin in the woods and the death of mimetic desire / Peter Y. Paik -- Eyes wide shut: mimesis and historical memory in Stanley Kubrick's The shining / David Humbert -- Against romantic love: mimeticism and satire in Woody Allen's Vicky, Cristina, Barcelona; you will meet a tall dark stranger; and To Rome with love / Scott Cowdell -- A beautiful crisis: Ang Lee's film adaptation of The ice storm / Carly Osborn -- Cowboy metaphysics, the virtuous-enough cowboy, and mimetic desire in Stephen Fears' The hi-lo country / Thomas Ryba -- Television. The self in crisis: watching Mad men and Homeland with Girard and Hegel / Paolo Diego Bubbio -- Media, murder, and memoir: Girardian baroque in Robert Drewe's The shark net / Rosamund Dalziell -- Conversion in Dexter / Matthew John Paul Tan and Joel Hodge